Pembinaan Nilai-Nilai Multikultural pada Masyarakat dalam Mengantisipasi Dampak Keberadaan Bandara Internasional Jawa Barat di Kecamatan Kertajati, Majalengka - Yoyo Zakaria Ansori; Indra Adi Budiman; Dede Salim Nahdi (Universitas Mathla'ul Anwar Banten, 2019)
FOSTERING MULTICULTURAL VALUES IN THE COMMUNITY IN ANTICIPATING THE IMPACT OF THE EXISTENCE OF THE WEST JAVA INTERNATIONAL AIRPORT IN KERTAJATI DISTRICT, MAJALENGKA. The phenomenon of diversity is like a double-edged knife, one side has a positive impact, that is, we have a rich diversity of cultural treasures, but the other side also has a negative impact, because diversity can trigger conflicts between community groups which in turn can cause instability in various fields. This is what was tried to be facilitated through fostering multicultural values ​​in the community as an anticipatory effort towards the impact of the existence of the West Java international airport in the Kertajati sub-district of Majalengka Regency carried out by the Community Partnership Program (PKM) team. The purpose of coaching activities is to increase the knowledge of multicultural values ​​and have the attitude of accepting other groups equally as a unit, regardless of cultural, ethnic, gender, language, or religious differences. The method used in this training includes the provision of material, discussion, question and answer, and the application of the value internalization model, namely the value analysis model.